Branding Awareness Sebagai Mediasi Pengaruh Pemasaran Digital Terhadap Keputusan Pembelian Generasi Z Kota Malang - Apriandana, Rizky Andrianto; Rokhman, M. Taufiq Noor; Kirom, Novita Rifaul (Manajemen & Bisnis Jurnal, 2025)
The purpose of this study was to determine and analyze the direct influence of brand awareness and digital marketing on purchasing decisions, and brand awareness on digital marketing. Furthermore, we analyzed brand awareness as a mediator of the influence of digital marketing on purchasing decisions. The analysis tool used was Smart PLS, with a sample of 106 Generation Z consumers who purchased products from the influencer Aghnia Cosmetic Products. The results showed that digital marketing directly influenced brand awareness and purchasing decisions for Byebadskin skincare products. Brand awareness can mediate the influence of digital marketing on purchasing decisions for Byebadskin skincare products.